Effect of Silver Nanoparticles on the Electrical Characteristics of Oxide/Semiconductor Heterojunctions. (23rd April 2019) - Rezk, Ayman; Abbas, Yawar; Saadat, Irfan; Nayfeh, Ammar; Rezeq, Moh'd
Abstract : The localized electrical effect of nanoparticles present in an oxide/semiconductor hetero-junction is investigated by means of Conductive Atomic Force Microscopy (CAFM) and Scanning Kelvin Probe Microscopy (SKPM). This study demonstrates the capability of the sandwiched NPs to modulate the oxide/semiconductor junction in both forward and reverse directions, thus enabling a distinct nano-scale heterojunction. This research, in turn, will contribute to the miniaturization of such NPs based devices in novel applications.